(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This paper explores the intricate relationship between the English language and culture through the lens of linguistic anthropology. It examines how English is used to express identity, social norms, and cultural values in various contexts. The study highlights the role of English in shaping social interactions, power dynamics, and media representation. Additionally, it discusses the diversity of English dialects and accents, emphasizing their cultural significance and the insights they provide into societal structures and cultural practices.